Kombinasi Pupuk Organik Cair Limbah Kulit Singkong Dan Kulit Bawang Sebagai Suplemen Materi Pengolahan Limbah Organik Berbasis Video Animasi - Nadila Ariani Syaumi; Waris; Ismul Mauludin Al Habib (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the nutrient content of liquid organic fertilizer (LOF) derived from a combination of cassava peel and onion peel waste, and to develop an animated video as supplementary material for learning organic waste processing. The method used was quantitative descriptive, involving the fermentation of organic materials, nutrient content laboratory testing, and media validation by experts in content, media, and language. The analysis results showed that nutrient contents such as organic-C (1.67%), total-N (0.08%), P₂O₅ (0.0025%), and K₂O (0.0048%) were still below the quality standards for LOF, with a pH of 3.31. Nevertheless, the developed animated video media received an average validation score of 94% and was rated as highly feasible for educational use. In conclusion, the animation-based video developed in this study can serve as an engaging educational alternative for teaching organic waste processing in high school. Keywords: Animated Video, Cassava Peel, Liquid Organic Fertilizer, Nutrients, Onion Peel